3K3A-activated protein C variant does not interfere with the plasma clot lysis activity of tenecteplase - Mukherjee, Purba (Stroke, 2020)
BACKGROUND AND PURPOSE —: A recombinant engineered variant of activated protein C (APC), 3K3A-APC, lacks anticoagulant properties (<10%) while preserving APC’s anti-inflammatory, anti-apoptotic, and neuroprotective functions and is very promising in clinical trials for ischemic stroke. Therapeutic intervention with single bolus administration of the third-generation tissue-plasminogen activator (t-PA), tenecteplase, is anticipated to be widely adopted for treatment of acute ischemic stroke. 3K3A-APC is well-tolerated in stroke patients dosed with alteplase and in vitro studies show 3K3A-APC does not interfere with alteplase-induced clot lysis. The purpose of this in vitro study was to assess the influence of 3K3A-APC on tenecteplase-induced clot lysis. METHODS —: Tenecteplase-mediated lysis of thrombin generated plasma clots of human normal pooled plasma was monitored in the presence of varying doses of 3K3A-APC. The effects on fibrinolysis by tenecteplase and alteplase were compared. RESULTS —: The presence of 3K3A-APC shortened the time for clot lysis induced by tenecteplase at very low levels but not at higher therapeutic concentrations of tenecteplase. Comparisons of alteplase-mediated clot lysis to tenecteplase clot lysis showed that both thrombolytic agents behaved similarly in the presence of 3K3A-APC. CONCLUSIONS —: These results indicate that 3K3A-APC does not interfere with tenecteplase’s clot lysis function.